Refining rehabilitation with proprioception training: expediting return to play - Laskowski, E. R.; Newcomer-Aney, K.; Smith, J. (The Physician and Sportsmedicine, 1997)
Although definitions of proprioception--sense of joint position--may vary, its importance in preventing and rehabilitating athletic injury remains constant: Restoring it after injury allows the body to maintain stability and orientation during static and dynamic activities. Any type of joint injury can interrupt position sense. Proprioceptive programs need to be tailored to the individual patient, but exercises can include balance training, closed-kinetic-chain exercises such as the leg press or single-leg hops, back-strengtheners, and quadruped stabilization. Sport-specific training is also crucial in regaining proprioception; an example is defensive slide drills in basketball.